A Cross-National Comparison of Education and Earnings - Inge O'Connor (Luxembourg Income Study (LIS), 1994)
This paper attempts to bridge the gap between previous cross-national work estimating rates of return to education and the current trend toward examining rates over time. Changes in the returns to education in the 1980s over five countries were driven by different forces across the countries.
Keywords: 330; Lohn; Berufsbildung; Humankapital; Australien; Deutschland; Kanada; Niederlande; USA